(untitled) (REMUNOM, 2023)
The hereby article intends to analyze if homeschooling is compatible with the Brazilian legal system, as well as analyze the Brazilian socioeconomic and educational scenario, the homeschooling´s practical implications, and what was decided by the Brazilian Supreme Court. As scientific methodology, documental and journalistic research were applied, such as legal, doctrinal and jurisprudential analysis.